Electrochemical advanced oxidation processes as decentralized water treatment technologies to remediate domestic washing machine effluents - dos Santos, Alexsandro Jhones; Costa, Emily Cintia Tossi de Araújo; da Silva, Djalma Ribeiro; Garcia-Segura, Sergi; Martínez-Huitle, Carlos Alberto [UNESP] (Springer Nature, 2018)
Water scarcity is one of the major concerns worldwide. In order to secure this appreciated natural resource, management and development of water treatment technologies are mandatory. One feasible alternative is the consideration of water recycling/reuse at the household scale. Here, the treatment of actual washing machine effluent by electrochemical advanced oxidation processes was considered. Electrochemical oxidation and electro-Fenton technologies can be applied as decentralized small-scale water treatment devices. Therefore, efficient decolorization and total organic abatement have been followed. The results demonstrate the promising performance of solar photoelectro-Fenton process, where complete color and organic removal was attained after 240 min of treatment under optimum conditions by applying a current density of 66.6 mA cm−2. Thus, electrochemical technologies emerge as promising water-sustainable approaches.
Keywords: Advanced oxidation processes; Azo dyes; Boron-doped diamond; Decentralized water treatment; Solar photoelectro-Fenton; Wastewater treatment